Analisis SWOT dalam Optimalisasi Branding Self Photo Studio Jatim Information Technology Creative Surabaya Sebagai Ujung Tombak Pendapatan bagi UPT PMPITK - Raden Burhanuddin Try Pratama Rahmatullah; Muchammad Ismail (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the optimization of self photo studio in Jatim Informaton Technology Creative (JITC) Surabaya as part of an effort to increase Local Original Income (PAD) by utilizing less productive government assets. JITC was initially a facility provided by the government, more precisely by the Department of Industry and Trade and managed by the UPT for Development of Industrial Product Quality and Creative Technology as a place for start-ups to develop. This study uses qualitative research methods with analytical techniques and SWOT analysis approaches to identify strengths, weaknesses, opportunities, and threats in managing service branding. Although this service is fully supported by the government, this service is still lacking in its development, therefore this study recommends the need to strengthen the branding strategy at the JITC self photo studio is very necessary in order to develop and contribute to increasing East Java PAD.